Callous-Unemotional Traits are Associated With Child-to-Parent Aggression. (November 2022) - Kuay, Hue San; Boothroyd, Lynda G.; Towl, Graham J.; Tiffin, Paul A.; Muñoz, Luna C.
This study examined the relations between callous-unemotional traits and perpetration of aggression toward parents in two separate studies, while also considering motivation for aggression and parenting styles experienced among young people. Study 1 involved 60 parents of children aged between 11 and 17 years old. The online study found high callous-unemotional traits, as reported by parents, to be associated with aggression toward both parents. Both types of motivation (proactive and reactive, as reported by parents) were associated with aggression toward parents. Study 2 involved 42 youths from an alternative education sample (between 11 and 16 years old). Youths with higher self-reported callous-unemotional traits reported more aggression toward both parents. Both studies, which had different reporters and different samples, showed youths with higher callous-unemotional traits were more aggressive toward their parents. In discussing the results, we note the importance of including callous-unemotional traits in future research on parent-directed aggression and in studies on domestic violence more broadly.